Inhibitory Effect of Polysaccharides of Marine Hydrobionts on Biofilm Formation - N. N. Besednova; I. D. Makarenkova; T. N. Zvyagintseva; T. A. Kuznetsova; T. S. Zaporozhets (Антибиотики и Химиотерапия)
In the review there are considered the recent data on the perspectives of the use of polysaccharides (PS) from marine hydrobionts for inhibition of formation of bacterial biofilms, which play a significant role in the onset and process of different infections, as well as for design of antiadhesive coatings on medical produce. Particular attention is paid to antiadhesive properties of natural PS from marine microorganisms, algae and invertebrate animals, which prevent formation of biofilms. Antibiofilm PS possess such positive characteristics, as biocompatibility and biodegradability, that is of great interest for medical and industrial applications. The possibility of simultaneous use of complexes of compounds of different chemical nature and mechanisms of action in infectious diseases, involving biofilm formation is of special interest. It is believed that biologically active substances from marine hydrobionts could serve as the basis for development of new antibiofilm drugs, including complex ones.